Integrated inverted pendulum and whole-body control design for bipedal robot with foot slip. Issue 37 (2022) - Mihalec, Marko; Han, Feng; Yi, Jingang
Abstract: Low-friction ground surfaces present a particular challenge for control of bipedal walking robots. The onset of foot slip changes the robot dynamics and the commonly designed walking controllers assuming non-slip conditions cannot maintain balance and prevent the walker from falling. We present a two-level robot controller for bipedal walker under foot slip. The high-level control is built on a two-mass linear inverted pendulum (TMLIP) model to generate the appropriate step location such that the robot walker maintains dynamic balance through multiple planned steps. The specified stepping tasks are fed to the low-level control that is based on a whole-body operational space (WBOS) framework. The WBOS controller uses the dynamic model of the multi-link bipedal walker and generates joint torques to maintain balance and follow the given stepping task in the presence of foot slip. Performance of the integrated TMLIP-WBOS control algorithm is demonstrated through extensive simulation studies of a 5-link robotic walker.